Bombesin staining in neuroendocrine cell hyperplasia of infancy (NEHI) and other childhood interstitial lung diseases (chILD). Issue 4 (13th April 2015) - Yancheva, Slaveya G; Velani, Asha; Rice, Alexandra; Montero, Angeles; Hansell, David M; Koo, Sergio; Thia, Lina; Bush, Andrew; Nicholson, Andrew G
Abstract : Aims: We have analysed levels of bombesin‐positive neuroendocrine cells (NECs) in neuroendocrine cell hyperplasia of infancy (NEHI) and other childhood interstitial lung diseases (chILDs) in order to validate proposed histological criteria for NEHI and investigate its aetiology. Methods and results: The extent of bombesin‐positive cells within airway epithelium was analysed in lung biopsies from seven patients diagnosed with NEHI, including two classified previously as non‐diagnostic, and other chILDs ( n = 64) with age ranges of 1 month–18 years. NECs were counted and calculated as a percentage of airways containing NECs, average percentage of NECs per airway, percentage of airways with >10% NECs and number of neuroendocrine bodies (NEBs). Correlation with age and gender was also undertaken. Patients with NEHI had the highest average percentage of bombesin‐positive NECs per airway compared to other chILDs. However, NEH was also seen in many other chILDs, and appears to be most prominent in disorders associated with lung immaturity such as histological patterns associated with surfactant protein‐related disorders and pulmonary interstitial glycogenosis. Conclusions: NEH may, to a degree, be a marker of airway immaturity rather than the direct cause of NEHI. This possibility is supported by the fact that the number of bombesin‐positive NECs decreased with age in this cohort, independent of disease type. The average percentage of bombesin‐positive NECs per airway appears to be the best histological criterion for assessing the extent of NECs in the context of NEHI.